After Brecht: the Impact (Effects, Affects) of Intermedial Theatre - Nelson, Robin (Intermédialités / Intermediality, 2008)
AbstractThis article addresses claims made about the impact of intermedial theatre with reference to examples of contemporary practice. In particular it makes references to Brecht in this context and differentiates between Brechtian politics and aesthetics. The professed aim of intermedial practitioners to dislocate the bearings of experiencers of their work and to afford new perceptions by means of a radical play between mediums appears to resonate, at the level of principles of composition, with Brecht’s “radical separation of the elements.” However, at the level of politics, Brecht’s drama sought a broader understanding of isolated individuals by inviting audiences to see their experience in connection with a total historical process. But, regarding the Marxist trajectory in which Brecht’s practice was located, the context changed markedly post-1968, and beyond recognition post-1989. The article thus proposes that a new formulation is required of the impacts of new perceptions elicited by contemporary intermedial practices and ends with a brief consideration of Rancière’s account of the clash of heterogeneous elements in intermedial practice.